Synthesis of methods of evaluation of electromagnetic compatibility of radio-technical systems - Лукова-Чуйко, Наталія; Наконечний, Володимир; Сайко, Володимир Григорович; Толюпа , Сергій (Київський національний університет імені Тараса Шевченка, 2019)
Modern development of radio equipment is characterized by an increase in the speed of processes of transmission and processing of information, miniaturization and integration into unified complexes that physically bridles the sources and receptors of interference. All this leads to the strengthening of the requirements to ensure compliance with the conditions of electromagnetic compatibility and the need for its evaluation at the design stage of radio engineering devices and systems, because the incomplete or incorrect assessment of these requirements leads to a significant increase in time and material costs of the manufacturer, for further development of the development of electronic equipment and reduction its competitiveness. Widespread use of different purposeful electronic means leads to an increase in the levels of electromagnetic fields created by them in the surrounding space. These fields are obstacles for other similar devices, may degrade the operating conditions and reduce the effectiveness of their use. In this process, it is easy to see the characteristic features of dialectical development - progress in this area is restrained by the negative phenomena generated by its development. Further progress requires the overcoming of this trend, that is, development on a new quality level, which is to ensure the joint operation of various means. The key is that the actions of the electromagnetic fields, which are created by some technical means to the other, are carried out for the transmission of information, its processing, or vice versa, violation of the process of transmission and processing of data. Therefore, an analysis is proposed that allows preliminary prediction of the fulfillment of the conditions of electromagnetic compatibility in a group of radio-electronic means that have a number of sources of interference and radio engineering devices on which they affect. In this case, the important issue of checking the provision of electromagnetic compatibility of radio-electronic means is to determine the magnitude of the permissible power at which provides electromagnetic compatibility. The purpose of this article is to consider, from the general positions, the main tasks of the analysis and evaluation of the electromagnetic compatibility of radio-electronic means.

Сучасний розвиток радіотехнічних засобів характеризується зростанням швидкодії процесів передачі й обробки інформації, мініатюризацією та інтеграцією в єдині комплекси, що фізично зближує джерела і рецептори перешкод. Все це призводить до посилення вимог щодо забезпечення виконання умов електромагнітної сумісності і до необхідності її оцінювання на стадії проектування радіотехнічних пристроїв і систем. Неповна або невірна оцінка цих вимоги приводить до значного зростання часових і матеріальних витрат виробника, на подальше доопрацювання розроблювальної електронної апаратури і зниження її конкурентоспроможності. Широке використання різних за призначенням радіоелектронних засобів призводять до зростання рівнів електромагнітних полів, що створюються ними в навколишньому просторі. Ці поля є перешкодами для інших подібних пристроїв, можуть погіршувати умови функціонування і знижувати ефективність їх застосування. Цей процес має характерні риси діалектичного розвитку - прогрес в цій області стримується негативними явищами, породженими її розвитком. Подальший прогрес вимагає подолання цієї тенденції, тобто розвитку на новому якісному рівні, що полягає в забезпеченні спільного функціонування різних електронних засобів. Принциповим є те, що дії електромагнітних полів, які створюються одними технічними засобами на інші, здійснюються для передачі інформації, її обробки, або навпаки, порушення процесу передачі і обробки даних. Тому в роботі запропонований відповідний аналіз, що дозволяє проводити попереднє прогнозування виконання умов електромагнітної сумісності в групі радіоелектронних засобів, які мають деяке число джерел перешкод і радіотехнічних пристроїв на які вони впливають. При цьому, важливим питанням перевірки забезпечення електромагнітної сумісності радіоелектронних засобів є визначення величини припустимої потужності при якій забезпечується умова електромагнітної сумісності. Метою даної статті є розгляд, із загальних позицій, основних завдань аналізу та оцінювання електромагнітної сумісності радіоелектронних засобів.
Синтез методів оцінювання електромагнітної сумісності радіотехнічних систем
Keywords: electromagnetic field; electromagnetic compatibility; intentional interference; radio engineering system; radio electronic means; conditions of electromagnetic compatibility; електромагнітне поле; електромагнітна сумісність; навмисні перешкоди; радіотехнічна система; радіоелектронні засоби; умови електромагнітної сумісності